IMPLEMENTASI SYNTHESIA AI DALAM PENGEMBANGAN VIDEO PEMBELAJARAN ANIMASI UNTUK MENINGKATKAN KOMPETENSI LITERASI DIGITAL GURU - Febbry Romundza; Afrida Afrida; Asmiyunda Asmiyunda; Hendra Hendra; Dwi Rahayu Siregar; Fadilla Ulfah (Jurnal Pengabdian Masyarakat Khatulistiwa, 2025)
ABSTRACTThe rapid development of Artificial Intelligence (AI) has created new opportunities in education, particularly in the development of digital learning media. One of the most innovative applications is Synthesia AI, a platform that enables the creation of animated learning videos with virtual avatars and multilingual automated narration. This study aims to implement the use of Synthesia AI in developing animated instructional videos as an effort to improve teachers’ digital literacy competence. The research employed a descriptive qualitative approach with several stages: needs analysis, teacher training in using Synthesia AI, video production, and evaluation through observation, questionnaires, and interviews. The results indicated that more than 85% of teachers reported increased confidence in creating digital media, 78% were able to design appropriate learning scripts for AI-based videos, and 82% successfully produced animated instructional videos that were engaging, interactive, and curriculum-oriented. Furthermore, teachers’ digital literacy competence improved in four aspects: technological literacy, information literacy, media literacy, and digital pedagogy. These findings highlight that the integration of AI can serve as a practical and innovative solution for teachers to deliver more adaptive, creative, and relevant learning experiences that meet the needs of 21st-century students.Keywords : Synthesia AI, animated instructional video, digital literacy, teachers, artificial intelligence.ABSTRAKPerkembangan teknologi kecerdasan buatan (Artificial Intelligence/AI) telah membuka peluang baru dalam dunia pendidikan, khususnya dalam pengembangan media pembelajaran digital. Salah satu aplikasi yang inovatif adalah Synthesia AI, sebuah platform yang memungkinkan pembuatan video animasi pembelajaran dengan avatar virtual dan narasi otomatis multibahasa. Penelitian ini bertujuan untuk mengimplementasikan penggunaan Synthesia AI dalam pembuatan video pembelajaran animasi sebagai upaya meningkatkan kompetensi literasi digital guru. Metode penelitian menggunakan pendekatan deskriptif kualitatif dengan tahapan: analisis kebutuhan, pelatihan guru dalam penggunaan Synthesia AI, produksi video pembelajaran, serta evaluasi melalui observasi, angket, dan wawancara. Hasil penelitian menunjukkan bahwa lebih dari 85% guru merasa lebih percaya diri dalam membuat media digital, 78% mampu menyusun naskah pembelajaran yang sesuai untuk diintegrasikan ke dalam video AI, dan 82% menghasilkan video pembelajaran animasi yang dinilai menarik, interaktif, dan sesuai kurikulum. Selain itu, kompetensi literasi digital guru meningkat pada aspek teknologi, informasi, media, dan pedagogi digital. Temuan ini menegaskan bahwa pemanfaatan AI dapat menjadi solusi praktis dan inovatif bagi guru untuk menghadirkan pengalaman belajar yang lebih adaptif, kreatif, dan relevan dengan kebutuhan siswa abad ke-21.Kata kunci : Synthesia AI, video pembelajaran animasi, literasi digital, guru, kecerdasan buatan